Local vs. long-range sources of aerosol particles upon Ny-Ålesund (Svalbard Islands): mineral chemistry and geochemical records - Moroni, B; Cappelletti, D; Crocchianti, S; Busetto, M; Mazzola, M; Becagli, S; Traversi, R; Udisti, R.; FERRERO, LUCA (Rendiconti Lincei, 2016)
Aerosol samplings were performed both at ground level and at different heights upon the Ny-Ålesund polar station in June–July 2012 using a tethered balloon equipped with a sampling pump and meteorological sensors. The samples were analyzed by ion chromatography and scanning electron microscopy to characterize the sources and the evolution of the aerosol particles in the planetary boundary layer. The results show the main contribution of long-range over local/regional transported particles and sediments in the aerosols in the period of interest. Among the long-range sources, a main contribution was represented by Siberian local soils and regional wildfires which provided typical particles (metal oxides, calcareous grains), and ion species (nss-K+, nss-SO42−) to the aerosols. Among the local sources, a main contribution was represented by fly ash emitted by the cruise ships frequently landing around Ny-Ålesund during summer. Another aspect which results from aerosol particle characterization is the clear stratification of the planetary boundary layer upon Ny-Ålesund. This typical feature, which has been already documented in spring on the same site (Moroni et al. 2015), is quite effective also in summertime despite the higher potential of local dust production and the lower atmospheric stability characterizing this period.